The perfect review school - Magdato, Joy Lyn T.; Ong, Jathniel Elison L.; Sorongon, Christopher P.; Sorongon, Cus D.; Umadhay, Lemuel M.; Villanueva, Annie Rose G. (2009)
Every graduating accountancy student is faced by a serious problem of choosing the best review school that will maximize his/her potential of passing the Certified Public Accountants licensure exam. In the course of choosing the best review school, several factors have to be considered. Among these factors are financial aspect, academic performance, environmental, and familial support. Under each of these general factors are specific variables that will be used to test the level of relevance and importance that will determine the perfect review school for the student. the dependent variable considered is the Review School. In conducting the study, a total of 154 respondents (all graduating accountancy students) from four different universities were used as samples. The survey was conducted with the use of questionnaires. Each questionnaire contained questions about different general factors and their specific variables that are believed to affect the choice for a review school. Out of 154 respondents, only 84 responded to the survey. The results of the study show that there is a strong overall correlation between the variables considered and the choice for Review School, computed using linear regression. This study showed that thee is a strong overall correlation between the variables considered and the choice for Review School computed using linear regression. This study showed that the financial, academic, environmental, and familial factors can have a positive and significant influence to a student's choice of a Review School. This study further reveals that in order to improve the strength as to how different variables affect the choice of a Review School, more variables aside from the items already listed in this study have to be identified and included.
[Research Paper] (BA 199-Business Research). -- [Iloilo City] : UPV-CM, March 13, 2009.